Moving the Needle with Lean OKRs : Setting Objectives and Key Results to Reach Your Most Ambitious Goal. - den Haak, Bart. (Business Expert Press, 2021)
Lean OKRs presents insightful anecdotes, creative exercises, clear figures and step-by-step models. Designed as a comprehensive guide, it covers everything from theoretical roots to practical execution, including company-wide strategy alignment and emotional management. Applicable to small companies as well as large organizations, Lean OKRs drives innovation through behavioral changes, empowering and motivating teams through focused daily OKR practices that are simple to put into action. Practical and to the point, this book integrates a unique combination of structural and leadership strategies, resulting in a new approach to OKRs that conquers the hurdles experienced by most business leaders today.